2023
DOI: 10.3389/fmicb.2022.1074382
|View full text |Cite
|
Sign up to set email alerts
|

Naso-oropharyngeal microbiome from breast cancer patients diagnosed with COVID-19

Abstract: Due to immunosuppressive cancer therapies, cancer patients diagnosed with COVID-19 have a higher chance of developing severe symptoms and present a higher mortality rate in comparison to the general population. Here we show a comparative analysis of the microbiome from naso-oropharyngeal samples of breast cancer patients with respect to SARS-CoV-2 status and identified bacteria associated with symptom severity. Total DNA of naso-oropharyngeal swabs from 74 women with or without breast cancer, positive or negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…In pancreatic cancer (PC), the alteration of gut microbiota caused by COVID-19 infection showed an impact on PC progression via immune regulation [118]. Recently, it was demonstrated that patients with cancer and COVID-19 have a higher chance of severe symptoms, suggesting an association between the naso-oropharyngeal microbiome, breast cancer, and COVID-19 severity [119]. In patients with lung cancer, the relationship between COVID-19 and lung cancer has also been explored.…”
Section: Covid-19 and Lung Cancermentioning
confidence: 99%
“…In pancreatic cancer (PC), the alteration of gut microbiota caused by COVID-19 infection showed an impact on PC progression via immune regulation [118]. Recently, it was demonstrated that patients with cancer and COVID-19 have a higher chance of severe symptoms, suggesting an association between the naso-oropharyngeal microbiome, breast cancer, and COVID-19 severity [119]. In patients with lung cancer, the relationship between COVID-19 and lung cancer has also been explored.…”
Section: Covid-19 and Lung Cancermentioning
confidence: 99%